English and Slovak Compounds - Malekova, Danica (Communications - Scientific letters of the University of Zilina, 2002)
The article comments on how differently English and Slovak languages reflect the extra-linguistic reality. This is proved by the different status of English and Slovak compounds supplemented by some examples from legal terminology.